2023
DOI: 10.1002/cbic.202200600
|View full text |Cite
|
Sign up to set email alerts
|

The Laccase of Myrothecium roridum VKM F‐3565: A New Look at Fungal Laccase Tolerance to Neutral and Alkaline Conditions**

Abstract: Most of the currently known fungal laccases show their maximum activity under acidic environmental conditions. It is known that a decrease in the activity of a typical laccase at neutral or alkaline pH values is the result of an increase in the binding of the hydroxide anion to the T2/T3 copper center, which prevents the transfer of an electron from the T1 Cu to the trinuclear copper center. However, evolutionary pressure has resolved the existing limitations in the catalytic mechanism of laccase, allowing suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Conventional detoxification methods for mycotoxins involve physical, chemical, and microbial approaches. , However, these methods possess drawbacks such as nutrient loss, reagent residues, and secondary pollution to the environment. , In contrast, enzymatic degradation offers advantages, including mild reaction conditions, high efficiency, low cost, and convenient operations. , Fungal laccases (EC 1.10.32) have attracted considerable attention due to their environmentally friendly characteristics and catalytic properties, such as high oxidation–reduction potentials, wide temperature ranges, and maximum activity under acidic conditions. , These characteristics make them suitable for use in food and feed environments . To date, several studies have reported the efficiency of laccases from fungi and bacteria in degrading AFB 1 and ZEN.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional detoxification methods for mycotoxins involve physical, chemical, and microbial approaches. , However, these methods possess drawbacks such as nutrient loss, reagent residues, and secondary pollution to the environment. , In contrast, enzymatic degradation offers advantages, including mild reaction conditions, high efficiency, low cost, and convenient operations. , Fungal laccases (EC 1.10.32) have attracted considerable attention due to their environmentally friendly characteristics and catalytic properties, such as high oxidation–reduction potentials, wide temperature ranges, and maximum activity under acidic conditions. , These characteristics make them suitable for use in food and feed environments . To date, several studies have reported the efficiency of laccases from fungi and bacteria in degrading AFB 1 and ZEN.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 These characteristics make them suitable for use in food and feed environments. 18 To date, several studies have reported the efficiency of laccases from fungi and bacteria in degrading AFB 1 and ZEN. Zhao et al reported that Bacillus licheniformis laccase CotA was able to degrade 39% of the AFB 1 and 70% of the ZEN.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our team has found fungi producing oxidases that are the most active in relation to phenolic compounds and phenylpropanoids under slightly alkaline environmental conditions (at pH 7.0-9.0): Rhizoctonia solani VKM F-895, Myrothecium verrucaria VKM F-3851, Myrothecium roridum VKM F-3565, and C. geniculata VKM F-3561 [26,27]. Alkaliphilic laccase of the fungus M. roridum VKM F-3565 was isolated and characterized [28]. A novel proton channel has been observed in its molecule as well as in molecules of known alkaliphilic fungal laccases, which provide the transfer of protons to the T2/T3-copper cluster necessary for functional activity of the enzyme under neutral and alkaline environments [28].…”
Section: Introductionmentioning
confidence: 99%
“…Alkaliphilic laccase of the fungus M. roridum VKM F-3565 was isolated and characterized [28]. A novel proton channel has been observed in its molecule as well as in molecules of known alkaliphilic fungal laccases, which provide the transfer of protons to the T2/T3-copper cluster necessary for functional activity of the enzyme under neutral and alkaline environments [28].…”
Section: Introductionmentioning
confidence: 99%